(untitled) (Journal of Business and Economics, 2026)
The Government of Ghana has announced plans to develop a 1,200 MW state-owned thermal power plant to utilise additional domestic natural gas and strengthen long-term electricity security. Although the proposal may support industrialisation, gas monetisation and system adequacy, its financing, ownership and risk-allocation architecture will determine whether it becomes a productive national asset or another source of fiscal and energy-sector distress. This paper evaluates the proposed project through the lenses of project finance, public–private partnerships, contingent-liability management, energy economics and power-sector governance. It adopts a qualitative policy-analytical case-study methodology, drawing on Ghanaian energy statistics, fiscal and regulatory documents, international infrastructure-finance literature and comparative electricity-sector experience. The analysis finds that wholly sovereign-financed development would expose Ghana to concentrated construction, financing, operational, foreign-exchange and demand risks, while a conventional privately financed independent power producer model backed by unconditional take-or-pay commitments could merely convert direct public debt into contingent liabilities. The paper proposes a Strategic Risk-Sharing Power Expansion Framework based on phased combined-cycle development, limited and predominantly in-kind public equity, substantial private capital at risk, capped payment-security instruments, performance-based power-purchase arrangements, diversified domestic and regional revenues, independent project-company governance and transparent fiscal-risk reporting. It concludes that risk sharing should not mean equal risk distribution: each material risk should be allocated to the institution best able to control, mitigate or absorb it at the lowest economic cost.